MODEL MATEMATIKA UNTUK MASALAH TRANSPORTASI LEBIH DARI SATU PRODUK [MATHEMATICAL MODELS FOR TRANSPORTATION PROBLEMS INVOLVING MORE THAN ONE PRODUCT] - Lina Cahyadi (Universitas Pelita Harapan, 2022)
Distribution companies need to plan efficient shipments to avoid incurring large shipping costs. Therefore, a company that addresses transportation problems by choosing the right distribution pattern can obtain optimal distribution costs. The transportation problem model is applied to allocate the same product to the destination places. In the problem of distributing more than one product, the transportation problem model is modified so that it can be used to optimize shipping costs. This study aimed to optimize distribution costs using a modified transportation problem model. The data obtained from the